Synthesis of ?-MnO2@Mn2O3 and ?-MnO2 nanoparticles using tartaric/maleic acid and their enhanced performance in the catalytic oxidation of pulp and paper mill wastewater - Sugesti, Heni; Prawiranegara, Barata Aditya; Utama, Panca Setia; Saputra, Edy (Journal of Applied Materials and Technology, 2024)
Two MnOx, namely ?-MnO2@Mn2O3 and ?-MnO2 catalyst, were successfully synthesized using two different organic acids, tartaric and maleic acid, as a reduction in the redox process of KMnO4. The obtained catalysts are used in the AOP degradation reaction for paper mill effluent. The organic content in the effluent is analogous to the COD number in the effluent. The degradation process is depicted as a decrease in the COD number. The catalyst properties were characterized using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), and N2 sorption. The obtained materials were then studied for PMS activation using Oxone® as a sulfate radical source for COD removal reactions. The ?-MnO2@Mn2O3, which is compromised by Mn (IV) and Mn (II, III), by using 0.3 gL-1 ?-MnO2@Mn2O3 has the best efficiency with almost 75% COD removal, higher than the ?-MnO2 catalyst. The activation energy of the ?-MnO2@Mn2O3 is measured up to 11.4 kJ mol-1.